An analysis of International Baccalaureate – English Language Curriculum for Middle Year Program - Geby Devtiana Maryono; Emi Emilia (Master Program in Linguistics, Diponegoro University, 2022)
The IB Curriculum, which was initially founded in Switzerland, is used globally. Many schools in Indonesia also apply this curriculum, and the number keeps growing. This paper will present the results of a study aiming to investigate the ideology, model, and elements of the International Baccalaureate (IB) curriculum, specifically the English (Language Acquisition) curriculum for the Middle Year Program (secondary school). The study has been given shape by the theory of curriculum development. The study employed a case study research design, especially text analysis. The results show that the English IB curriculum applies a learner-cantered ideology with collaborative learning to build students’ communicative skills. It also has been influenced by a deductive model proposed by Tyler. Moreover, the elements also confirm Tyler’s rationale, consisting of objectives, the content, learning activities or learning experiences designed to achieve the objectives various types of assessments and evaluations.